The risk aspects of Halal products and services towards tourists’ attitude and behavioural responses - Supian, Kamisah; Muhammad Yunus, Ida Farina; Ahmad, Aznita; Syed Abdullah, Sharifah Hilmi; Abdul Rauf, Reeny Karlina; Alias, Zuraini (Penerbit UiTM, 2022)
Tourists’ perceptions of risk aspects for travel destinations are one of the key elements in deciding to revisit and suggest tourism destinations. A few studies have been made on the implications and inclination of tourists revisiting and suggesting a destination. However, a theoretical foundation needs to be developed in current literature, highlighting the impact of tourist risk of halal products and services through satisfaction toward sintention to recommend and continue the use of halal items. This paper aims to increase the understanding of the intention to recommend and continue the use of halal items given the identified sources of risk and the mediating role of tourist satisfaction for sustainable tourism in Klang Valley. This research examines a comprehensive model of intention to recommend and continue using halal items. Researchers conducted a study through structured questionnaires to Klang Valley tourists. The data of 461 respondents have been analysed using Partial Least Square Structural Equation Modelling (PLS-SEM). The findings show all elements of risk aspects positively influence the intention to recommend and continue the usage of halal items. Furthermore, tourist satisfaction mediates the relationship between risk aspects and the intention to recommend and continue the usage of halal items. Results from this study will help tourism providers react accordingly to the tourists’ needs by understanding the importance of halal products and services in an atmosphere of commercial competition. Moreover, the findings provide insights into distinct risk perceptions that destination planners can leverage to tailor business strategies to meet the quality expectations of tourists